If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -1r = 43 Solving 18 + -1r = 43 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -1r = 43 + -18 Combine like terms: 18 + -18 = 0 0 + -1r = 43 + -18 -1r = 43 + -18 Combine like terms: 43 + -18 = 25 -1r = 25 Divide each side by '-1'. r = -25 Simplifying r = -25
| f(x)=100(5)*x | | X+(5x)=120 | | 12.67+42.35x=5.34+26.25 | | 3x^2+100x=212 | | x+43=-16 | | 5(2x+4)=(9x+4) | | 9=-2X-5+B | | -4x-10x+5= | | 9x+4=-86 | | 7x+13x-4=5(4x-4) | | 9b+9b=72 | | -0.7+0.5+12x=0.5x+0.8 | | -1.2x+11+2.6x= | | 9x+4=86 | | 9X+3=3X | | 218=119-x | | 7.30=4x+6 | | 4r+3=10 | | 1.3x-5.4x-5.4x+3= | | 35-3x=10+6x | | 1.3h-4(2.3h-3)=2.3h-6 | | 5x+7y=300solvey | | 2(5z+2)-3(z+1)= | | -11r-3+12r+2= | | 0=2x^2-3x-104 | | x+x+3=31 | | 12x=10+2 | | z=(x-4)k | | 8r^3+24r^2=32r | | 2.2n+4-9-4.5n= | | 6y(6-x)= | | -4m+14=-2m-10 |